Maritime Transport in the Spanish Economy in the Decades of Consolidation of Democracy (1975–1995) - Zamarreño-Aramendia, Gorka; Ruiz-Romero-de-la-Cruz, Elena María (IOAP-MDPI, 2022)
This research analyzes the traffic of goods through the ports managed by the Port Authorities of the Spanish port system from the beginning of democracy in Spain to the end of the 21st century; a period that shows the effects on maritime transport as a result of the political changes that have taken place and the new regulations that have been applied, highlighting the 1992 Port Law, which would facilitate the transition from the port as an integrated center for international trade to the port as a logistics platform. We have used primary sources from the Spanish State Port’s archives and have consulted statistical yearbooks, commercial reports and the yearbooks of the National Statistics Institute (INE). This research allows us, through the data of the traffic of goods by presentation and the GVA at market prices, to quantify the transformation of the group of state-owned ports and their impact on the Spanish economy. Until now, speculation has focused on the share of freight traffic and its value at this time of transition in the Spanish economy, as well as the actual contribution it made to inflation in the period under study.
Keywords: Historia económica; Economic history; Port management; Spanish port system; Shipping traffic